Application of Air Source Heat Pump System for Floor Heating during Winter - Wang Tiejun; Xu Wei; Zeng Xiaocheng; Liang Tao; Xia Xingxiang; Hu Peng (Zhileng xuebao)
A 3P variable frequency air source heat pump unit was developed and applied in a residential building with floor radiant heating. The system was tested during the winter over a 93d period. The range of the outdoor environment temperatures was ﹣10 ℃ to 16 ℃, with the average value being 3.72 ℃. The heat capacity of the heat pump was 3.82 to 10.06 kW, with the average value at 6.71 kW. The average suction and discharge pressures were 0.55 and 2.28 MPa, respectively, and the compression ratio of the system was small. The energy efficiency ratio (EER) range was 2.32 to 4.71, and the aver?age value of EER was 3.46, indicating a high level of energy efficiency. The temperatures at the height of 0.1, 1, 1.5, and 2 m were measured indoors, and the average values were 20.48, 19.26, 18.75, and 18.01 ℃, respectively; therefore, the temperature field was comfortable because of the negative gradient. The results in the warmest day and coldest day were compared and it is indicated that the average outdoor temperature difference in the two days was 17.21 ℃, and that the heating capacity and EER in the warmest day were 41.9% and 159% of those in the coldest day, respectively. The system showed good environmental adaptability and comfort. Compared with an urban central heating system and a gas-fired boiler heat?ing system, the operating costs were reduced by 39.82% and 56.17%, respectively, and the energy efficiency, safety, and thermal comfort were improved.